Influence of Ionic Liquids on the Aggregation and Pre-aggregation Phenomena of Asphaltenes in Model Solvent Mixtures by Molecular Dynamics Simulations and Quantum Mechanical Calculations - Celia-Silva, Lucas G. (2022)
This work presents a systematic study of asphaltene pre-aggregation phenomena in the absence and in the presence of ionic liquids (ILs) from the family of 1-alkyl-3- methylimidazolium by molecular dynamics simulations. The effects of the alkyl chain length of the cation (studying ILs with alkyl chains between C4 and C10) and of the dimension of the anion (testing chloride and bromide) on the aggregation behavior of asphaltenes have been studied. To correlate the results obtained with the direct interaction between each additive and asphaltene, the latter was investigated both by the analysis of the radial distribution functions obtained by molecular dynamics simulations and quantum mechanical calculations. The DFT method was used to calculate the relative stability of the asphaltene-ionic liquid dimers and also the energy, shape, and spatial distribution of frontier orbitals. It was found that all the ionic liquids studied present a dispersing effect on asphaltene in model solvents, except for mixtures rich in toluene where, in most cases, the opposite effect is observed. This is accompanied by the interaction intensity as measured by radial distribution functions. The effects of the alkyl side chain length of the cation and of the anion radius are subtler, but it seems that the asphaltene dispersion effect increases with the length of the cation’s alkyl side chain and decreases with the radius of the anion; these effects are more clearly observed in the mixtures richer in n-heptane. These trends were corroborated by DFT calculations, which showed that the energetic stability of the asphaltene-additive dimer is as higher as the alkyl chain is longer and the anion is smaller. Preaggregation phenomena were also studied in mixtures containing CO2, which proved to be a precipitating agent as observed experimentally. The relative performances of the IL studied were not altered by the presence of CO2.